An abstract approximate controllability result and applications to elliptic and parabolic systems with dynamic boundary conditions - Ioan Bejenaru; Jesus Ildefonso Diaz; Ioan I. Vrabie (Electronic Journal of Differential Equations, 2001)
In this paper we prove an approximate controllability result for an abstract semilinear evolution equation in a Hilbert space and we obtain as consequences the approximate controllability for some classes of elliptic and parabolic problems subjected to nonlinear, possible non monotone, dynamic boundary conditions.